The Effectiveness of Differentiated Learning Approach within PBL Model to Improve Students Critical Thinking Skills - Agusmaliani Agusmaliani; Noldy Pelenkahu; Elisabeth Z. Oroh (Journal of English Culture, Language, Literature and Education, 2025)
This study aims to determine the effectiveness of the Differentiated Learning Approach within the Problem Based Learning PBL model in improving students critical thinking skills in English particularly on the topic of analytical exposition text among grade XI students of SMA Negeri 2 Tondano This study employed a quantitative method using a quasi experimental design of the Non Equivalent Group Design type The sample consisted of class XI A as the experimental group and XI B as the control group each with 20 students selected through random sampling Data collection techniques included pre test post test observations and documentation Data were analyzed using the t test to examine the effect off Differentiated Learning approach within PBL to students Critical Thinking The results revealed a significant difference between the experimental and control classes Students in the experimental group who received instruction using the Differentiated Learning Approach within the PBL model showed notable improvement The average pre test score in learning achievement increased from from 58 45 to 83 20 The t test showed a significance value of 0 000 lt; 0 05 These findings demonstrate that the Differentiated Learning Approach within the Problem Based Learning model is effective in enhancing students critical thinking skills particularly in learning English analytical exposition texts < p>